Endpoint attachment of unfractionated vs low molecular weight heparin: a comparative study on blood compatibility - Stephan Harm; Jennifer Zottl; Claudia Schildböck; Christoph Bauer; Denisa Cont; Denisa Cont; Viktoria Weber (Frontiers in Materials)
IntroductionBlood compatibility is a critical requirement for materials used in medical devices to prevent adverse reactions such as thrombosis and inflammation. Heparin, a natural anticoagulant, is commonly used to coat medical devices such as catheters and stents, mimicking the endothelial glycocalyx and thereby preventing thrombus formation. While endpoint attached (EPA) heparin surfaces have proven effective in clinical use, concerns have arisen regarding heparin-induced thrombocytopenia (HIT) associated with unfractionated heparin (UFH)-bonded prostheses. Given the lower HIT risk profile of low molecular weight heparin (LMWH), this study aimed to evaluate the blood compatibility of LMWH-functionalized surfaces in comparison to those functionalized with UFH.MethodsConventional 96-well plates and adsorbent materials were functionalized with either UFH or LMWH. The blood compatibility of these surfaces was assessed by analyzing coagulation parameters, platelet adhesion, and leukocyte adhesion. Antithrombin III (AT-III) binding was also examined to understand the anticoagulant mechanism of LMWH-functionalized surfaces.ResultsLMWH-functionalized surfaces demonstrated no significant binding to AT-III. Despite this, both LMWH- and UFH-functionalized surfaces effectively prevented the activation of coagulation triggered by foreign surfaces. Furthermore, there was no observed increase in platelet or leukocyte adhesion on LMWH-functionalized surfaces compared to UFH-functionalized ones, indicating a similar degree of blood compatibility between the two.DiscussionThis study highlights that LMWH can provide blood compatibility comparable to that of UFH when used for surface functionalization, despite its lack of AT-III binding. These findings support the potential of LMWH as a safer alternative to UFH in medical device coatings, particularly in applications where the risk of HIT must be minimized.